Entanglement of the Formal and Informal in Everyday Surrogacy Negotiations: The Case of Georgia - Mariam Darchiashvili; Elene Gavashelishvili (Studies of Transition States and Societies, 2023)
With surrogacy-friendly legislation and relatively affordable reproductive services, Georgia has become one of the centres of surrogacy worldwide. Despite the legality of surrogacy, the scarcity of legislation leaves this field largely unregulated. Georgian law regulates only the preand post-procedural periods of surrogacy, and the surrogacy process is almost entirely omitted from the legal framework. In this article, we explore how surrogacy is regulated and managed in everyday life in Georgia. A closer examination shows that to manage the process efficiently, agencies and clinics create their own fluid regulations that, on the one hand, are based on global guidelines but, on the other hand, reflect the shared norms relevant in the Georgian context. The paper is largely based on a study of surrogacy clinics and agencies in Tbilisi and Batumi during 2020 and 2022. Our study revealed the sizeable role informalities have in everyday surrogacy negotiations. Moreover, these informalities are not separate but entngled with formal regulations and institutions. We explored the complementary, compensating, and enabling character of informalities for formalities both at the institutional (agencies and clinics) and the individual level (intended parents and surrogate women).